Implementasi Penilaian Portofolio Pada Pembelajaran Matematika Berbasis Cooperative Learning Tipe Stad Untuk Meningkatkan Hasil Belajar Siswa Kelas Viii Smp Muhammadiyah 1 Sukoharjo Tahun 2016/2017 - Cahyaningsih, Nur; , Dr. Sumardi, M.Si (2017)
ABSTRACT This research aims to improve the result of students mathematics learning through the implementation of portfolio assessment in based on cooperative learning STAD type. Based on its approach, the research is a qualitative research with the design type action (PTK). The research subjects from class VIII C study of SMP Muhammadiyah 1 Sukoharjo which were 25 students. Techniques of data collection using interviews, observation, tests, field notes, and documentation. The validity of the data using source technic triangulation. Data analysis technique is done by data reduction, data presentation, and conclusion. The result showed an increase of the indicators as follows: 1) many students who complete KKM (>50%); 2) Student skills complete LKS (no students are in the less category); 3) Student attitudes during group discussions (no students are in the less category); 4) Student's daily behaviour during the learning process (All of aspect > 50%). Conclusion this research is through the implementation of portfolio assessment in based on cooperative learning STAD type can improve the result of students mathematics learning from class VIII C SMP Muhammadiyah 1 Sukoharjo 2016/2017 academic year. Keywords: implementation, portfolio assessment, mathematics learning, stad, learning outcomes.